DIVIDENDS ON NON-CUMULATIVE PREFERRED STOCK. - Briggs, L. L. (The Accounting Review, 1933)
Abstract This article discusses the topic of dividends on non-cumulative preferred stock. The development of the corporation into a dominant form of business organization, has added new complications to capital structures such that the problem of preserving a proper balance between the holders of various classes of securities in their competition for income is becoming more and more difficult to solve. The preservation of this balance by the adjustment of relationships among the groups owning corporate shares is an extremely delicate and arduous task for the courts. So far as dividends are concerned, preferred stock may be classified as cumulative and non-cumulative. On the other hand, the holders of non-cumulative preferred stock are entitled to no dividends for any particular year if there are no earnings for that period. A problem arises when profits are sufficient to pay a dividend to this class of shareholders but the board of directors refuses to make a distribution for that year and invests the earnings in fixed improvements or retains them as working capital.